1995
DOI: 10.1021/np50115a009
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolites of Ophiobolin A and Antimicrobial Evaluation of Ophiobolins

Abstract: Ophiobolin A [1], 3-anhydroophiobolin A [2], ophiobolin B [3], and ophiobolin L [4] were isolated from fermentation broths of Cochliobolus heterostrophus. Preliminary screening showed that a number of organisms were capable of metabolizing the sesterterpene ophiobolin A [1]. Large-scale transformations of ophiobolin A [1] with Polyangium cellulosum produced 6 and 7 while Pseudomonas aeruginosa produced 8. Resting-cell preparations of Penicillium patulum afforded 9 and 10. The structures of these metabolites we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
62
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 12 publications
9
62
0
Order By: Relevance
“…1), by comparison of their spectroscopic properties, essentially the 1 H and 13 C NMR and MS data. Their physical and spectroscopic data were very similar to those reported in the literature Li et al, 1995;Sugawara et al, 1988). The fourth ophiobolin (8, Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…1), by comparison of their spectroscopic properties, essentially the 1 H and 13 C NMR and MS data. Their physical and spectroscopic data were very similar to those reported in the literature Li et al, 1995;Sugawara et al, 1988). The fourth ophiobolin (8, Fig.…”
Section: Resultssupporting
confidence: 85%
“…b Multiplicities determined by DEPT spectrum. c These assignments can be exchanged (they were made by comparison with analoguesLi et al, 1995).…”
mentioning
confidence: 99%
“…According to our knowledge, only ophiobolin A was shown to have antifungal activity against Gloeosporium, Glomerella, Corticium, Macrosporium, and Trichophyton (Nakamura & Ishibashi 1958). Additionally, it demonstrated growth inhibition of A. flavus, Candida albicans, Torulopsis cremoris, and T. petrophilum (Li et al 1995).…”
Section: Resultsmentioning
confidence: 93%
“…For comparison, in the case of the opportunistic human pathogen Rhizopus oryzae , MIC values with complete blockade of growth were found in the ranges of 2–4, 2–4 and 0.5–2 μg mL –1 for amphotericin B, miconazole and itraconazole, respectively, whereas nystatin, griseofulvin and fluconazole exerted only a minimal inhibition effect on the fungus (Nyilasi et al , 2010; I. Nyilasi, unpublished data). In another study, MICs of ophiobolin A against A. flavus and C. albicans were found to be 25 and 12.5 μg mL –1 , respectively (Li et al , 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier study, ophiobolin A was found to inhibit the growth of Gloeosporium, Glomerella, Corticium, Macrosporium and Trichophyton species (Nakamura & Ishibashi, 1958). It also showed a potent inhibitory effect against Aspergillus flavus, Candida albicans, Torulopsis cremoris and Torulopsis petrophilum (Li et al , 1995). Similarly, both ophiobolins A and B exerted strong activity against Trichophyton mentagrophytes in an agar‐well diffusion assay (Au et al , 2000a).…”
Section: Introductionmentioning
confidence: 99%